Avaliação do cenário de compra e venda de resíduos sólidos recicláveis nos Municípios do CONDOESTE/ES - Dutra, Renato Meira de Sousa (2016)
In spite of the recycling is a viable alternative to minimize the impacts caused by the production of municipal solid waste, for its empowerment it becomes necessary to identify the recycling market, with projections of production's supply and demand to define strategies, resources and reliable local conditions. Thefore, this study had as goal to evaluate the current and future buying and selling of recyclable solid waste in 16 cities of state of Espírito Santo. The research identified through the application of interviews (Surveys), fieldresearch and secondary data collection that while relying on poor infrastructure and dependence on Government subsidies, the 12 surveyed pickers organizations can forward 9.1% of recyclable waste from selective collection to recycle with an average productivity of screening of 109 kg/picker/day with an average payment of R $ 945.00/picker/month. From the methodology proposed by Damásio (2010a, 2010b), 17% of organizations surveyed were classified as medium efficiency, as opposed to 82% of them operating with very low efficiency. For the adequacy and expansion of screening capacity of scavengers organizations (infrastructure and equipment), to a scenario of 100% selective collection in the cities surveyed, would be required investments of 16.5 million reais,which could be paid by the savings from the current 6 million reais spent per year with the disposal of recyclable waste to landfill. This investment also allows the creation of 467 new jobs, representing growth of 402% for the insertion of pickers in theformal the employment market. Regarding the consumer market, few recycling companies have been identified in the region, which may justify the low price paid for the waste. The market for recyclable Espírito Santo is formed mostly by micro and small enterprises, which generally cary out the activities of collection, transportation, screening and marketing of waste.About supplier market, the industry, followed by pickers organizations and junky yard, and in fourth place individual pickers, were the typicalsources of recyclable identified in Espírito Santo.